ANALISIS ALTERNATIF PENGGUNAAN LAHAN UNTUK MENJAMIN KETERSEDIAAN AIR DI DAS KONAWEHA PROVINSI SULAWESI TENGGARA - La Baco S; Naik Sinukaban; Yanuar J Purwanto; Bunasor Sanim; Suria Darma Tarigan (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2011)
Title : The Analysis of Land Use Alternatives to Ensure Water Supply at Konaweha Watershed Southeast Sulawesi Province. Fenomena  of decreasing  water supply and increasing  water demand occurred at Konaweha watershed.   Konaweha  watershed  shed is a priority watershed  in Southeast  Sulawesi  Province due to its crucial function. Land use changes were suspected to be the cause of decreasing water supply. One effect of this condition  was maximum  discharge  increase  and minimum  discharge decrease of Konaweha River resulted in water deficit.   Research objectives were (1) to evaluate the effect of land use changes on hydrologic condition of Konaweha watershed;  (2) to evaluate the water supply and water demand as well as supply and demand water balance at Konaweha watershed,  and  (3) to  formulate  land  use  alternatives  and  management  policy  of Konaweha watershed.   This research had been conducted at Konaweha watershed for 10 months e.g. from June  2009  to March  2010.  The average  declining  of forest  width  during  1991‐1999  was  1.25 percent/year,  2001‐2005  was 0.52 percent/year  and 2006‐2011  was 0.90 percent/year.  In the same time the availability of minimum discharge as a water supply was decrease. There was no deficit on annual water supply until 2050 but monthly distribution  of hydrograph  caused water deficit in September started from 2016.  Proportion of maintenance  cost for watershed function at  Kendari  Municipality  was  35  percent  while  at  the  District  of  Konawe,  South  Konawe  and Kolaka were 28 percent,  15 percent, and 22 percent  respectively  from total economic  value of water  at  Konaweha   watershed.   Forest  economic   value  including   flora  and  fauna,  carbon absorption,  option value, bequest  value and existence  value was IDR 14,974,716/hectare.  Five alternative  of  land  use  at  Konaweha  watershed  were:  (1)  Scenario  1:  30  percent  forest,  45 percent plantation, 6 percent mix garden and 1 percent bush; (2) Scenario 2: 35 percent forest, 45 percent  plantation,  5 percent  mix  garden  and  1 percent  bush;  (3)  Scenario  3:  44  percent forest,  35  percent  plantation,  5  percent  mix  garden  and  1  percent  bush;  (4)  Scenario  4:  34 percent forest, 45 percent plantation, 7 percent mix garden and 1 percent bush; and (5) Scenario 5: 40 percent forest, 35 percent plantation, 5 percent mix garden and 2 percent bush. Scenario 4 were  not  appropriate   while  scenario  1,  2,  3  and  5  were  appropriate  to  applied  in  upper Konaweha  watershed.  Scenario 3 with a minimal of 44 percent of forest was the best land use alternative.Keywords: watershed, land use change, water supply, water demand